2022
DOI: 10.1088/1361-648x/ac6307
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids in conducting nanoslits: how important is the range of the screened electrostatic interactions?

Abstract: Analytical models for capacitive energy storage in nanopores attract growing interest as they can provide in-depth analytical insights into charging mechanisms. So far, such approaches have been limited to models with nearest-neighbor interactions. This assumption is seemingly justified due to a strong screening of inter-ionic interactions in narrow conducting pores. However, how important is the extent of these interactions? Does it affect the energy storage and phase behavior of confined ionic liquids? Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Surprisingly, the Bethe-lattice approximation showed an excellent quantitative agreement with Monte Carlo simulations of the same model (symbols and lines in Figure 6c−e). 43 Most recently, Groda et al 78 revealed that next-to-nearest and higher neighbor interactions in eq 23 can lead to the emergence of large-scale mesophases that have not been reported before.…”
mentioning
confidence: 98%
“…Surprisingly, the Bethe-lattice approximation showed an excellent quantitative agreement with Monte Carlo simulations of the same model (symbols and lines in Figure 6c−e). 43 Most recently, Groda et al 78 revealed that next-to-nearest and higher neighbor interactions in eq 23 can lead to the emergence of large-scale mesophases that have not been reported before.…”
mentioning
confidence: 98%
“…Figure c depicts a lattice model with the Hamiltonian H plasma = 1 / ( 4 π ϵ o ϵ 80 ) i j 2 N q i q j / | R i j | with equal numbers of monovalent ( q = ±1) cations ( i , j ≤ N ) and anions ( i , j > N ), no checkerboard constraint, no double occupancy, and no lattice water. Lattice models for electrolytes have been previously studied, ,, but to our knowledge not their static dielectric properties. ϵ 80 = 80 strongly screens the Coulomb interactions between the dilute charged lattice particles with a size of 4.5 Å.…”
mentioning
confidence: 99%
“…Ions are crowded where they are most important [184,259] in many systems beyond ion channels and so these issues have attracted much attention in the literature of nanosystems, artificial channels, super capacitors, and so on. Reviews of Jinn-Liang Liu provide a gateway to the immense literature on finite volume effects [186,267] but work is so active [268][269][270], and the literature is expanding so rapidly, that readers must depend on their own searches of the literature. Finite size effects are important in more or less any application involving ions.…”
mentioning
confidence: 99%